Optical Transmitters based on High-Order Surface Grating Lasers for Applications in Communication Systems - Jain, Gaurav (Trinity College Dublin. School of Physics. Discipline of Physics, 2021)
Optical communication is the forefront of modern communication systems and is unarguably the leading technology for information sharing and transmission of large amounts of data over longer distances with low latency. Since its inception in early 1970s, the transmission capacity of optical networks have experienced an exceptional growth, thanks to various technological advancements. Alongside, the information age is thriving with the advent of personal computers and more recently media-rich applications and services. It is expected that within a decade, the continuous exponential growth in the data traffic will outrun the system capacity. To keep pace with the rapidly increasing data traffic, continual industry innovation is needed to increase the system capacity. This calls for technologies and photonic components able to continually improve the spectral efficiency of the already deployed optical networks. In that endeavour, in this thesis we have explored three unique transmitter designs. The first transmitter is based on non-uniform high-order surface gratings which enable simple and high-yield fabrication along with superior operation at higher temperatures compared to previous designs. The second transmitter is an optical frequency comb based on the gain-switching of an externally injected laser diode. External injection allows for the generation of multiple discernible comb tones with high spectral purity. The third transmitter considered in this thesis is a unique directly modulated Photonic Integrated Circuit (PIC) utilising optical injection by incorporating a master-slave configuration. Optical injection reduces the frequency chirp of the directly modulated PIC and allows the transmission of the optical signal up to longer distances by mitigating the dispersion effects in the standard single mode fiber.
APPROVED
Keywords: photonic integrated circuit; direct modulation; transmission; Multicarrier transmitter; single mode laser; athermalisation; high-order surface grating; automation; multi period slotted Fabry-Perot laser; optical frequency comb; gain switching; optical external injection; injection locking